GAMBARAN PENGETAHUAN IBU HAMIL TENTANG KELAS IBU HAMIL DI PUSKESMAS PLUPUH I - RITA RIYANTI KUSUMADEWI; Luluk Fajria Maulida (Viva Medika, 2018)
Background: Maternal mortality can caused of during pregnancy, childbirth and after giving birth. Many government programs have been including the book mother and child health, love mother movement, making pregnancy safer ( Kartini, 2017 ).Class pregnant women was one of love mother movement with the hope that it will play a role in reduce pain and death for pregnant women, maternity mother and mother parturition. A successful training / learning can be seen from the input, the process, output, the impact, evaluasidan environment. A preliminary study done found data pregnant women in the puskesmas plupuh i about 165 pregnant women, while for knowledge of classes pregnant women only part of pregnant women who know, and activities class pregnant women has rarely been implemented. The purpose of this research to know an illustration of the distribution knowledge pregnant women of classes pregnant mothers in puskesmas Plupuh I . Methods: The research is the kind of research descriptive research , to make an overview of situation or occurrence . Population research is pregnant mothers in puskesmas plupuh i attended a class pregnant women . The sample of the used 30 people . An instrument used is chief . Result: the research of the 26 respondents , distributed flattened of the respondents of knowledge enough as many as 13 respondents ( 50 % ) and knowledgeable less as many as 13 respondents ( 50 % ) . Conclusions: respondents awareness of class prosentase pregnant women having equal who know enough and less knowledgeable , with the rest of 13 respondents ( 50% ).